Enterprise, entrepreneurship and small business - Down, Simon (SAGE, 2010)
This textbook covers core themes and topics in the study of enterprise and looks at subjects that are often ignored, such as criminal entrepreneurs. It explores the processes of entrepreneuring, managing small enterprises, and the implications of working in an entrepreneurial corporation